Correlation of PROMIS Physical Function, Pain Interference, and Depression in Pediatric and Adolescent Patients in the Ambulatory Sports Medicine Clinic. Issue 6 (24th June 2019) - Makhni, Eric C.; Meldau, Jason E.; Blanchett, Jacob; Borowsky, Peter; Stephens, Jeffrey; Muh, Stephanie; Moutzouros, Vasilios
Background: Recently, interest has increased in incorporating the National Institutes of Health Patient-Reported Outcomes Measurement Information System (PROMIS) outcomes into clinical and research applications in sports medicine. The PROMIS forms have not been studied in pediatric and adolescent sports medicine patients. Purpose/Hypothesis: The goal of this study was to determine the correlation between PROMIS Computer Adaptive Test (CAT) forms measuring physical function, pain interference, and depression in pediatric and adolescent patients seen in the ambulatory sports medicine clinic. We hypothesized that there would be a negative correlation between physical function and pain interference as well as depression, as has been demonstrated in adult patient populations. Study Design: Cross-sectional study; Level of evidence, 3. Methods: All patients aged 8 to 17 years seen by 3 shoulder and sports medicine providers were included in this study. Patients completed a series of PROMIS CAT forms at clinic visits, including the PROMIS-PF and PROMIS-UE (Physical Function and Upper Extremity; depending on the nature of the complaint), PROMIS-PI (Pain Interference), and PROMIS-Depression subscales. Pearson correlation coefficients were calculated between the PROMIS forms as well as with other patient demographic data. Results: A total of 236 patient visits (152 patients) were included in the study, comprising 712 total PROMIS CAT forms. A negative correlation was found between PROMIS-PF and both PROMIS-Depression ( R = –0.34) and PROMIS-PI ( R = –0.76). These correlations with PROMIS-Depression and PROMIS-PI were –0.21 and –0.75, respectively, when considering the PROMIS-UE CAT. Patient demographic information had minimal impact on PROMIS scores as well as on correlations between scores. Conclusion: Correlations between physical function, pain interference, and depression were found to be similar in pediatric patients as they are in adult patients, as measured by PROMIS CAT forms.